Implementation of Da’wah Methods in Islamic Education Learning - Wirmanhanizon, Wirmanhanizon; Risa Septia Monika; Mulyani, Ridha; Rozalia Putri , Peni (Ahlussunnah: Journal of Islamic Education, 2023)
This research aims to determine the preparation of preaching methods in Islamic religious education learning which is used in implementing the preaching method in learning Islamic religious education at Junior High School 3 Tigo Nagari, Pasaman Regency. Then to find out the presentation of the preaching method in learning Islamic religious education at Junior High School 3 Tigo Nagari, Pasaman Regency and to find out the supporting and inhibiting factors in learning Islamic religious education at Junior High School 3 Tigo Nagari, Pasaman Regency. This research uses a descriptive qualitative approach. Data collection techniques: observation, interviews, and documentation. After all the data was collected, the author carried out classification, editing, and adjustments to the character and type of each data, then filtered it into a final conclusion. Based on the results of research conducted by the author, it shows that the implementation of the Preaching Method in Islamic Religious Education Learning at Junior High School 3 Tigo Nagari Pasaman Regency can be seen from various aspects including the Preparation of preaching methods in learning Islamic religious education, namely by impromptu method, memorization method, note reading method, and extemporaneous method. The presentation of the preaching method in Islamic religious education learning is so that the delivery of the material can run smoothly as the implementation of the preaching method is the delivery of learning material by means of speaking so that the lecture is quality as a learning method. Conduct evaluations to determine students' ability to master the learning material that has just been presented or given.